2019
DOI: 10.1016/j.trgeo.2019.100281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze-thaw cycles on mechanical strength of lime-treated fine-grained soils

Abstract: Lime treatment is a widely-used technique for the stabilization and improvement of finegrained soils in earthworks for transportation. In cold regions, lime treatment can be considered as an appropriate method to improve freeze-thaw resistance of fine-grained soils. The effectiveness of treatment can depend on soil nature, lime dosage and curing time. In the present work, three soils (silt of low plasticity, clay of low plasticity, and silt of high plasticity) were treated at three lime contents (lower, equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…After freeze-thaw cycles, an important index to gauge soil resistance to erosion, the shear strength of three soils significantly decreased, being supportive to most previous studies showing that soil structure becomes looser, and the mechanical properties and microstructure of soils change significantly [43][44][45][46][47]. Soil cohesion was determined by the tensile forces of menisci at the particle contact surfaces as well as the contact relationships between solid particles and liquid films [15].…”
Section: Effect Of Freeze-thaw On Soil Propertiessupporting
confidence: 75%
“…After freeze-thaw cycles, an important index to gauge soil resistance to erosion, the shear strength of three soils significantly decreased, being supportive to most previous studies showing that soil structure becomes looser, and the mechanical properties and microstructure of soils change significantly [43][44][45][46][47]. Soil cohesion was determined by the tensile forces of menisci at the particle contact surfaces as well as the contact relationships between solid particles and liquid films [15].…”
Section: Effect Of Freeze-thaw On Soil Propertiessupporting
confidence: 75%
“…In areas experiencing seasonal frost, to improve the mechanical behaviour under FT conditions, some effective and reliable techniques have been reported, such as adding cement, lime, fly ash, and fibre to the soil. Nguyen et al (2019) found the FTCs significantly decreased the mechanical strength of the samples and lime treatments were used to improve the FT resistance of fine-grained soils by X-ray computed tomography observations. The addition of both bassanite and coal ash improved the strength and durability of the stabilised soils significantly, and retained 65-85% strength after the first to second FTC compared to corresponding non-frozen stabilised soils and when no additives were used, it was about 50% (Shibi & Kamei 2014).…”
Section: Soil Mechanical Propertiesmentioning
confidence: 95%
“…Generally, when the soil structure becomes looser, the mechanical properties and microstructure of the soil change significantly (Figure 2), and additional deformation occurs when external pressure exceed the gravity stress after the FTCs (Liu et al 2016;Karumanchi et al 2020). However, additive components could improve the strength behaviour of FT soils, though the reinforcing mechanism is still not fully understood (Nguyen et al 2019;Liu et al 2020).…”
Section: Soil Mechanical Propertiesmentioning
confidence: 99%
“…Additional deformation occurred when external pressure exceeded gravity stress. However, additive (e.g., lime, fibers, quartz sands and sodium silicate et al) can improve the strength behavior of frozen-thawed soil, and the reinforcing mechanism was still not fully understood [77,78].…”
Section: Soil Propertiesmentioning
confidence: 99%